PAKISTAN INDIA RELATIONSHIP IN THE PERSPECTIVE OF CULTURAL DIPLOMACY (2008-2015) - Ahmad Raza; Sadia Noreen (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article focuses on the cultural diplomacy perspective of two rival South Asian countries, Pakistan and India. It describes how cultural relations are a key avenue in promoting peace and restoring diplomatic relations between the two nations, from cricket diplomacy after the two nations resumed relations in the 1950s to current efforts towards film, theatre, and literature. However, cultural interchanges have become crucial in breaking barriers and misunderstandings, which are attributes of political development. The article also looks at the Human development and gender emergence profile of the two countries and compares areas of similarities and differences. It highlights the performative nature of cultural analyses in the 21st-century socio-political climate, especially in the conflict between religion and politics. The article provides hope for improving relations between Pakistan and India and the importance of civil society organizations and individuals.